2013
DOI: 10.1590/s1415-43662013000200003
|View full text |Cite
|
Sign up to set email alerts
|

Curvas de compactação de um Latossolo Vermelho-Amarelo: com e sem reúso de amostras

Abstract: RESUMOA curva de compactação do solo é determinada pelo ensaio de Proctor, normal ou modificado, amplamente empregado na engenharia civil; entretanto, seu uso agronômico apresenta limitações já que a configuração da curva parte do reúso de uma única amostra, desconsiderando a estrutura original do solo. Diante disto, objetivou-se avaliar a configuração da curva de compactação a partir do reúso e não reúso de amostras de um Latossolo Vermelho-Amarelo considerando-se diferentes sistemas de manejo. Verificou-se, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
6

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 15 publications
0
6
0
6
Order By: Relevance
“…Several authors have stressed the importance of organic matter in determining soil quality because it influences, among other properties, the stability of the aggregates and the structure of the soil (HICKMANN et al, 2012;RAMOS et al, 2013); the rate of water infiltration and retention (RAWLS et al, 2003); biological activity and cation exchange capacity (SILVA; MENDONÇA, 2007); the complexation of metals (BEZERRA et al, 2009); the cycling and availability of nutrients to plants (SILVA et al, 2009); and the release of CO 2 and other gases (LAL;BRUCE, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have stressed the importance of organic matter in determining soil quality because it influences, among other properties, the stability of the aggregates and the structure of the soil (HICKMANN et al, 2012;RAMOS et al, 2013); the rate of water infiltration and retention (RAWLS et al, 2003); biological activity and cation exchange capacity (SILVA; MENDONÇA, 2007); the complexation of metals (BEZERRA et al, 2009); the cycling and availability of nutrients to plants (SILVA et al, 2009); and the release of CO 2 and other gases (LAL;BRUCE, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The M optimal value indicates where traffic of machinery should be avoided, because the increase in water content makes the soil easier to compact. In contrast, according to Ramos et al (2013), reduction in the water content can cause stronger coherence of the particles, making the soil less susceptible to compaction. Based on this, it was found that the gravimetric water contents that resulted in the highest compaction density in each soil layer were approximately 5% below the volumetric moisture equivalent to the field capacity (θCC = 10 kPa) for each layer, that is, by substituting the values in the water retention equations (Table 2) (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…This would make it unnecessary to determine the LLWR for each type of soil, because it would be sufficient to estimate the RBD value and use 0.90 as the upper threshold. However, it is important to standardize the method for determining the compaction curve to obtain the maximum soil density, preferably without reuse of samples for considering the soil structure, as urged by Ramos et al (2013). In this study, the proportion of the BD or RBD values ≥ BD critical (LLWR = 0) for the depths of 0.20 to 0.30 m and 0.30 to 0.40 m were, respectively, only 8 and 2% of the 117 samples collected.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations